Use of Anti-transcriptional Intermediary Factor-1 Gamma Autoantibody in Identifying Adult Dermatomyositis Patients with Cancer: A Systematic Review and Meta-analysis - Marion Best; Nicolas Molinari; François Chasset; Thierry Vincent; Nadège Cordel; Didier Bessis (Medical Journals Sweden, 2018)
Anti-transcriptional intermediary factor-1γ (TIF-1γ) autoantibody may be associated with cancer in adult patients with dermatomyositis. The aim of this study was to evaluate the risk of cancer in the presence of anti-TIF-1γ autoantibody in adult dermatomyositis. A comprehensive database search of EMBASE, MEDLINE and the Cochrane Library up to May 2018 was performed using the main key words "dermatomyositis", ""myositis", "inflammatory myopathies" and "anti-TIF-1". Eighteen studies, with a total of 1,962 dermatomyositis, were included in the meta-analysis. The pooled prevalence of cancer-associated dermatomyositis in patients with anti-TIF-1γ autoantibody was 0.41 (95% confidence interval (CI) 0.36-0.45). In the presence of anti-TIF-1γ autoantibody, the overall diagnostic odds ratio of cancer was 9.37 (95% CI 5.37-16.34) with low heterogeneity (Cochran's Q: 14.88 (df = 17, p = 0.604); I2 = 0%). The results of this systematic review confirm that detection of anti-TIF-1γ autoantibody is a valuable tool to identify a subset of adult dermatomyositis patients with higher risk of cancer.